Effectiveness of computer‐assisted learning in sports dentistry: studies over a multiple‐year period and at two universities. (17th January 2021) - Shiota, Nana; Kinoshita, Atsuhiro; Sunaga, Masayo; Tanabe, Gen; Hayashi, Kairi; Churei, Hiroshi; Fukai, Tomoko; Matsumoto, Masaru; Yasui, Toshikazu; Ueno, Toshiaki
Abstract: Introduction: Insufficient educational resources on sports dentistry result in varying lecture implementations across dental schools, which cause knowledge gaps amongst students. Thus, a new interactive sports dentistry‐related computer‐assisted learning (CAL) module was created to facilitate dental school undergraduate students' education. This study compared the CAL module's learning effectiveness with conventional video lectures (VL) and assessed its effectiveness when used over several years at a university, and examined its validation in different university contexts, and students' perceptions. Materials and Methods: Participants were 305 fifth‐year students. Students from a university in Tokyo participated for 3 years and those from a university in Saitama for 1 year. In each year, the students were divided into two groups—CAL and VL. They studied their assigned modules in 20‐min lessons. A written test was administered to determine their knowledge acquisition levels, along with a questionnaire. Results: Two hundred sixty‐two consenting participants were included in the statistical analysis. The CAL groups' test scores at both schools were significantly higher than the VL groups' every year ( p  < .001). Furthermore, test results from all years revealed no gender differences or repetition of the school years at either school. Most students at both universities evaluated the CAL module as excellent. Conclusion: The interactive CAL module generated consistently strong results over multiple years, during which it was used by a diverse group of students at two universities. The students highly rated the module's learning process as well as its contents.